How Hotel Smartphone Applications Affect Guest Satisfaction in Applications and Re-use Intention? An Experiential Value Approach. Issue 2 (3rd March 2020) - Kim, Hyeongmin; Kang, Soonhwa; Song, Chanho; Lee, Myong Jae (Mj)
ABSTRACT: Today, more hotel companies attempt to use hotel apps to provide useful content about hotel facilities, events or promotions, and directions. By using experiential values in the context of hotel app experience, this study explores how hotel guests perceive hotel apps and what affects their satisfaction with those apps and their re-use intentions through Partial Least Squares Structural Equation Modeling (PLS-SEM). A total of 212 usable responses were collected for data analysis through an online survey. The results of structural analysis revealed that while service excellence and esthetic values from hotel app experiences influence guest satisfaction, the playfulness value does not. Theoretical and managerial implications are discussed.